The influence of virtual instructional leadership on teachers’ commitment: A Malaysian e-leadership case study - Hapini Awang; Mat Rahimi Yusof; Mohd Faiz Mohd Yaakob; Mohd Fairuz Jafar; Ramlan Mustapha; Kalipakiam Subramaniam (Institute of Advanced Engineering and Science, 2022)
The ability of instructional leadership practices in shaping positive school culture is well known. Similarly, it is also proven that this kind of school leadership could strengthen teachers’ commitment. However, the research tended to focus on conventional instructional leadership and the ability of virtual instructional leadership to produce such impact remains unclear. Therefore, this study investigated the influence of virtual instructional leadership on teachers’ commitment. Based on Meyer and Allen’s Organizational Commitment Model the research model developed and analyzed using partial least squares-structural equation modeling (PLS-SEM). The finding revealed a positive impact of principals’ virtual instructional leadership practices towards teachers’ commitment in schools. Despite this, the study also discovered that normative and continuous commitments are not the fit dimensions for teacher’s commitments in the context of virtual instructional leadership, which is quite shocking. Hence, this would be a fruitful area for further works.